Changing Consumer Behavior Paradigms : Does Gender and Marital Status Influence Grocery Shopping Behavior ? An Exploratory Study - Krishnamurti, Shivakumar; Gupta, Babeet (Indian Journal of Marketing, 2017)
The study examined the grocery shopping behavior of people living in and around Delhi, Chennai, and Bengaluru. A pre-designed questionnaire was used to collect the primary data (experiences) from 246 people residing in and around these three cities. The collected data was analyzed with the help of statistical tools such as averages, percentages, factor analysis, student's t - test, structural equation model, and correlation. The objectives of this study were as follows: to know the extent to which male and female respondents differed in their grocery shopping behavior ; to know the extent to which married and unmarried respondents differed in their grocery shopping behavior ; to know whether grocery shoppers were satisfied with their grocery shopping experience. The study revealed the following : A majority of the grocery shoppers did grocery shopping once a week and most of the surveyed shoppers indicated that they spent an hour grocery shopping during each visit. Although the respondents showed some differences in their grocery shopping behavior depending on their gender and marital status, there appeared to be many similarities in their grocery shopping behavior. Irrespective of their gender and marital status, grocery shoppers tended to make additional unplanned purchases after seeing products and deals at the store, liked to list specific private label/store brand items to buy, were keen to buy fresh and new stocks of items, and chose to shop at a particular grocery outlet where they got all their requirements.